Relationship between structure and magnetic behaviour in zno-based systems - Guglieri Rodriguez, Clara (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
This work studies the magnetic behavior of ZnO nanoparticles capped with different organic molecules and showing room-temperature ferromagnetism (RTFM). Of particular significance is the combination of element-specific X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD) techniques, which demonstrates the intrinsic occurrence of RTFM in these systems and indicates that it is not related to the 3-D states of the metallic cation but is relayed along the conduction band of the semiconductor. The discovery of room-temperature ferromagnetism (RTFM) in semiconductors holds great promise in future spintronics technologies.   Further results presented here include O K-edge XMCD studies, which demonstrate that the oxygen ions have a ferromagnetic response in these ZnO-based systems, providing the first direct support for claims regarding the appearance of oxygen ferromagnetism in oxide semiconductors at the nanoscale.